2004
DOI: 10.1123/japa.12.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Leg-Extension Strength and Chair-Rise Performance in Elderly Women with Parkinson’s Disease

Abstract: The lower extremity performance in elderly female patients with mild to moderate Parkinson's disease (PD; n = 12) and controls (n = 16) was compared. Isometric dynamometry and force-plate measurements were used. PD patients had lower (p < .05) bilateral (BL) maximal isometric leg-extension force (MF), BL isometric MF relative to body mass, and maximal rate of isometric force development than control participants. BL strength deficit was greater (p < .05) in PD patients than in controls. A significantly longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
61
1
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 46 publications
6
61
1
8
Order By: Relevance
“…8,13 In contrast to the isokinetic evaluations described, some studies have evaluated quantitative isotonic and isometric muscle strength. 7,14,15 To date, no reported study has evaluated the isokinetic strength of the hip, knee, and ankle joints together. Some limited studies, however, have evaluated muscle groups at different isokinetic velocities in the lower extremities, 13 as well as the correlation between muscle strength and clinical status, and muscle strength and falls, 9 among patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…8,13 In contrast to the isokinetic evaluations described, some studies have evaluated quantitative isotonic and isometric muscle strength. 7,14,15 To date, no reported study has evaluated the isokinetic strength of the hip, knee, and ankle joints together. Some limited studies, however, have evaluated muscle groups at different isokinetic velocities in the lower extremities, 13 as well as the correlation between muscle strength and clinical status, and muscle strength and falls, 9 among patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [15][16][17][18] have demonstrated that the strength of the lower extremity muscles of PD patients and regular exercise are associated with their capacity to perform of functional tasks, such as walking and sit-to-stand. They emphasized the importance of appropriate intervention for people with PD to improve and/or maintain functional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Diese erhöhte Bewegungsvariabilität der PD-Patienten kann auch bei der Gangzyklusdauer und der Schrittvariabilität nachgewiesen werden und wird mit der Störung des automatisierten Schrittlokomotors im Zentralnervensystem bei Parkinsonpatienten in Zusammenhang gebracht [15][16][17]. Dabei scheint ein Defizit der zentral gesteuerten Muskelaktivierungsprogramme (Muskel-Timing) vorzuliegen [18][19][20][21]. Bezüglich der Muskelschwäche mit reduzierter Kraftproduktion liegen Studien bei Parkinsonpatienten vor [13,21] …”
Section: Messdurchführungunclassified
“…Dabei scheint ein Defizit der zentral gesteuerten Muskelaktivierungsprogramme (Muskel-Timing) vorzuliegen [18][19][20][21]. Bezüglich der Muskelschwäche mit reduzierter Kraftproduktion liegen Studien bei Parkinsonpatienten vor [13,21] …”
Section: Messdurchführungunclassified